INITIATING SUSTAINABLE PERFORMANCE ON LANGUAGE CURRICULUM IMPLEMENTATION - Sumekto, Didik Rinan (MAGISTRA, 2012)
The fundamental measurement of language curriculum performance initially reflects to some supporting processes during its implementation, in which it involves the stakeholders progressively. It is a mutual understanding that the language curriculum implementation requires a highly collaborative dynamics to any existing changes in the society. The real commitment and consistence of implementing the curriculum, in the later, as one aspect criteria to measure its success. Therefore, schools as the most ultimate institution of implementing this curriculum will have a challenging task and responsibility to reach out and to prove the achievements with all resources availability and limitation. Keywords: curriculum, evaluation, educational reform, performance